2020
DOI: 10.7160/aol.2020.120410
|View full text |Cite
|
Sign up to set email alerts
|

‘Products Mapping’ of South Africa’s Agri-food trade with the EU28 and Africa

Abstract: This paper uses ‘products mapping’ tool based on the trade balance index (TBI) and Lafay index to investigate trade performance and competitiveness in food items between South Africa (SA) and the EU28 and Africa. The data for this analysis is obtained from the UNCTAD database. SA’s agri-food trade balance climbed from $1.5 billion in 2005 to $3.1 billion in 2017. The results support the conclusion that in bilateral trade, certain products have comparative advantages in relation to African markets despite compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…[25], Kita and Poczta [50], Ishchukova and Smutka [51], Rytko [26], Carraresi and Banterle [38], Juchniewicz and Lukiewska [39], Bojnec and Fertő [30,40], Cimpoies [52], Kita [33,34], Wijnands and Verhoog [53], Smutka et al [54], Szczepaniak [27,31], Ortikov et al [55], Verter et al [56], Zdrahal et al [57] and Pawlak [19,35,58,59]. All those studies refer to the competitive position of the agri-food sector of individual countries or groups of countries either on the world market or in specific bilateral relations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[25], Kita and Poczta [50], Ishchukova and Smutka [51], Rytko [26], Carraresi and Banterle [38], Juchniewicz and Lukiewska [39], Bojnec and Fertő [30,40], Cimpoies [52], Kita [33,34], Wijnands and Verhoog [53], Smutka et al [54], Szczepaniak [27,31], Ortikov et al [55], Verter et al [56], Zdrahal et al [57] and Pawlak [19,35,58,59]. All those studies refer to the competitive position of the agri-food sector of individual countries or groups of countries either on the world market or in specific bilateral relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By constructing the Widodo matrices Ortikov et al [55] observed that in 2000-2018 agri-food products exported from Uzbekistan were competitive with regard to Asian and CIS markets, while the ability to successfully compete on the other markets was limited. The same approach was also employed by Verter et al [56] and Zdrahal et al [57]. The former authors investigated the dynamics of comparative advantages in Nigerian agri-food trade with the EU in 1995-2017.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their proposals were the promotion of agri-food value chains and a more protective trade policy to increase self-sufficiency. Zdráhal et al [40] used a product mapping tool to assess South Africa's agri-food trade with the EU. South Africa turned out to be more competitive on the African markets compared to the EU-28 market.…”
Section: Regional and Country-level Analysesmentioning
confidence: 99%
“…The application of this measure together with TBI makes it possible to construct the matrix providing a synthetic assessment of the competitive position of an analyzed country in trade with specific products or groups of products on selected reference markets. Such a methodological approach was proposed for the first time by Widodo [74], and it has been used to assess specialization and competitive performance of the agricultural trade for Russia [75], the Czech Republic [76], and African nations with the EU [77,78]. To specify transatlantic relations, this method was applied by [52] to identify the comparative advantages of the Polish agri-food sector on the US market.…”
Section: International Competitiveness Of the Agri-food Sector In The...mentioning
confidence: 99%